Gender inclusive education in higher education: illusory or a necessity? - Abdul Majid, Hariyati Shahrima; Zubairi, Ainol Madziah (IIUM Press and IPPTN, 2009)
Introduction: Malaysia, which achieved its independence in 1957, has undergone incredible socio-economic changes that have brought about wealth to its citizens. The growth and development of the Malaysian economy can largely be attributed to the success of the Malaysian education system which has seen literacy rate increases from 80 per cent for men in 1980 to more than 90 per cent in 2000. Similar increase is also observed in women, albeit slightly lower; from 62 per cent in 1980 to 82 per cent in 2000 (Aminah, 1998). The Malaysian higher education system has also undergone great transfonnations in the last five decades with, to date, a two-fold increase in the number of government universities compared to before the turn of the century.